CUTANEOUS METASTASIS OF LUNG CANCER - Nguyen Manh, Hung; Quach Thi, Giang; Nguyen Thi Ha, Minh (Tạp chí Da liễu học Việt Nam, 2025)
Cutaneous metastasis from lung cancer is rare but should be ruled out in patients with suspicious skin lesions and a history of smoking or lung cancer. All types of lung cancer can metastasize to the skin, with varying clinical manifestations. The incidence of cutaneous metastasis in lung cancer patients ranges from 1-12%. In 20-60% of cases, skin lesions appear before or simultaneously with the diagnosis of the primary tumor. Skin lesions are typically nodular, mobile or fixed, hard or soft, solitary or multiple, and painless. Histologically, cutaneous metastases often show moderate to poor differentiation. Treatment for solitary cutaneous metastasis typically includes surgery alone or combined with chemotherapy and/or radiation therapy. If multiple skin lesions or metastases to other organs are present, chemotherapy is the primary treatment option. Cutaneous metastasis from lung cancer is associated with a poor prognosis, with an average survival time of around 5-6 months. In this report, we present a case of a 58-year-old male patient with these manifestations.